A Combinatorial Analysis of the Overlapping Generations Model - Clark, Stephen A. (Review of Economic Studies, 1981)
Journal Article A Combinatorial Analysis of the Overlapping Generations Model Get access Stephen A. Clark Stephen A. Clark University of Kentucky Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 1, January 1981, Pages 139–145, https://doi.org/10.2307/2297126 Published: 01 January 1981 Article history Received: 01 July 1979 Accepted: 01 May 1980 Published: 01 January 1981